High-definition transcranial direct current stimulation desynchronizes refractory status epilepticus - Darion B. Toutant; Hussam El-Alawi; Eun Hyung Choi; Natalie Wright; Manzuma Khanam; Bojan Paunovic; Ji Hyun Ko; Marcus C. Ng (Neurotherapeutics)
Recently, we showed that high-definition transcranial direct current stimulation (hd-tDCS) can acutely reduce epileptic spike rates during and after stimulation in refractory status epilepticus (RSE), with a greater likelihood of patient discharge from the intensive care unit compared to historical controls. We investigate whether electroencephalographic (EEG) desynchronization during hd-tDCS can help account for observed anti-epileptic effects. Defining desynchronization as greater power in higher frequencies such as above 30 ​Hz (“gamma”) and lesser power in frequency bands lower than 30 ​Hz, we analyzed 27 EEG sessions from 10 RSE patients who had received 20-minute session(s) of 2-milliamperes of transcranial direct current custom-targeted at the epileptic focus as previously determined by a clinical EEGer monitoring the EEG in real-time. During hd-tDCS, median relative power change over the EEG electrode chains in which power changes were maximal was +4.84%, −5.25%, −1.88%, −1.94%, and +4.99% for respective delta, theta, alpha, beta, and gamma frequency bands in the bipolar longitudinal montage (p ​= ​0.0001); and +4.13%, −5.44%, −1.81%, −3.23%, and +5.41% in the referential Laplacian montage (p ​= ​0.0012). After hd-tDCS, median relative power changes reversed over the EEG electrode chains in which power changes were maximal: −2.74%, +4.20%, +1.74%, +1.75%, and −4.68% for the respective delta, theta, alpha, beta, and gamma frequency bands in the bipolar longitudinal montage (p ​= ​0.0001); and +1.59%, +5.07%, +1.74%, +2.40%, and −5.12% in the referential Laplacian montage (p ​= ​0.0004). These findings are consistent with EEG desynchronization through theta-alpha-beta-gamma bands during hd-tDCS, helping account for the efficacy of hd-tDCS as an emerging novel anti-epileptic therapy against RSE.